2003
DOI: 10.1002/mrd.10259
|View full text |Cite
|
Sign up to set email alerts
|

Development of the meiotic step in testes of pubertal rats: Comparison between the in vivo situation and under in vitro conditions

Abstract: The present work aimed to compare some features of the meiotic process which develops in the testis of pubertal rats, in vivo and in vitro, paying special attention to the time-course of the phenomenon. The differentiation of spermatocytes was assessed in testes of 20- to 46-day-old rats and in tubule segments of 20- or 28-day-old rats cultured over a 4-week period. Very similar results were obtained in vivo and in vitro, during the first week of culture, when considering the changes in the cell populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
8
18
0
1
Order By: Relevance
“…This property of Sertoli cells might also explain, at least partly, the lower percentages of apoptotic germinal cells measured by TUNEL assay than by annexin V binding. These results fit quite well with the proportions of apoptotic germ cells determined by measuring the level of activated caspase 3 in freshly isolated germ cell preparations or in cultured seminiferous tubules (Perrard et al 2003). Many in vivo studies have shown that both FSH and testosterone decrease apoptosis of both PS and RS of the rat (Billig et al 1995, Brinckworth et al 1995 , Marathe et al 1995, El Shennawy et al 1998, but some of them did not produce statistically significant results (Saito et al 2000).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This property of Sertoli cells might also explain, at least partly, the lower percentages of apoptotic germinal cells measured by TUNEL assay than by annexin V binding. These results fit quite well with the proportions of apoptotic germ cells determined by measuring the level of activated caspase 3 in freshly isolated germ cell preparations or in cultured seminiferous tubules (Perrard et al 2003). Many in vivo studies have shown that both FSH and testosterone decrease apoptosis of both PS and RS of the rat (Billig et al 1995, Brinckworth et al 1995 , Marathe et al 1995, El Shennawy et al 1998, but some of them did not produce statistically significant results (Saito et al 2000).…”
Section: Discussionsupporting
confidence: 67%
“…Besides, several teams have now demonstrated that meiosis can proceed in vitro when mammalian spermatogenic cells are cocultured with Sertoli cells (Parvinen et al 1983, Weiss et al 1997, Hue et al 1998, Staub et al 2000, Lee et al 2001, Sousa et al 2002, Godet et al 2004. In rodents, the kinetics of the meiotic process is similar in vivo and during the first week of culture (Parvinen et al 1983, Perrard et al 2003, but the efficiency of the meiosis events is somewhat lower than in vivo; this can be explained partly by a higher proportion of apoptotic 1C cells in culture and a bottleneck at the transition from middle to late PS which would lead to the phagocytosis of PS by the Sertoli cells (Perrard et al 2003). Nevertheless, it has been shown recently that RS developed in vitro can produce normal offspring in the mouse (Marh et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture of seminiferous tubule segments was performed as previously described for 21-dayold rat seminiferous tubules (Hue et al 1998, Staub et al 2000, Perrard et al 2003, but omitting testosterone in the culture medium. Indeed, Boitani and co-workers (1993) have shown that, as opposed to FSH, testosterone has no effect on the preservation of the cellular morphology of testicular explants from immature rats.…”
Section: Preparation Of Sertoli and Germinal Cell Fractionsmentioning
confidence: 99%
“…Les systèmes développés au laboratoire ont été validés sur de nombreux points de la physiologie. Nous avons ainsi montré que l'ensemble du processus méiotique d'un mammifère peut se dérouler ex vivo [13] et que les caractéristiques de la méiose qui se déroule ex vivo sont très proches de ce qui se produit dans les testicules de rat à la puberté [14]. Par ailleurs, nous avons montré que les pourcentages de spermatocytes aux différents stades de la prophase I-l eptotène, zygotène, pachytène et diplotène 3 précoces qui synthétisent le TGF-1 en plus grande abondance [27], celles-là mêmes qui synthétisent le NGF [24].…”
Section: éTudes Physiologiques De La Spermatogenèse Dans Des Modèles unclassified